COVID-19 associated cognitive impairment: A systematic review. (July 2022) - Tavares-Júnior, José W.L.; de Souza, Ana C.C.; Borges, José W.P.; Oliveira, Danilo N.; Siqueira-Neto, José I.; Sobreira-Neto, Manoel A.; Braga-Neto, Pedro
Abstract: Introduction: COVID-19 has a wide range of clinical manifestations. Neurological manifestations in COVID-19 patients were demonstrated during the pandemic, including cognitive impairment. This study aimed to determine any relationship between COVID-19 and cognitive complaints, such as dementia, mild cognitive impairment (MCI), or subjective cognitive decline (SCD). Methods: We performed a systematic review of MEDLINE via Ebsco, Cochrane EMBASE, SCOPUS, and LILACS electronic databases of observational studies with COVID-19 patients confirmed by serology or PCR who developed new cognitive impairment or deteriorated from previous cognitive impairment after infection. This review protocol was recorded on PROSPERO with registration number CRD 42021241590. Results: A total of 3.520 articles were retrieved and read. Twenty-two studies were selected for our review. A wide range of cognitive assessment tools (n = 25) was used. The most described affected domains in these studies were executive functions, attention, and episodic memory. Thirteen studies showed a pattern of cognitive impairment in processing speed, inattention, or executive dysfunction assessed through working memory. Conclusion: This review highlights the high frequency of cognitive impairment after COVID-19 infection. However, we were unable to differentiate whether the cognitive impairment found corresponded to mild cognitive impairment or dementia through data from selected studies, and this issue serves as one objective of future studies to be addressed on this topic.